Mutational Analysis of Quinolone-Resistant Determining Region gyrA and parC Genes in Quinolone-Resistant ESBL-Producing E. Coli - Hamzah, Hairul Aini; Sirat , Rahmatullah; Mustafa Mahmud, Mohammed Imad A.; Baharudin , Roesnita (IIUM Medical Journal Malaysia, 2021)
Introduction: Co-resistance to quinolones among extended spectrum β[1]lactamase (ESBL)-producing E. coli commonly occurs in clinical settings. Quinolones act on DNA gyrase and DNA topoisomerase enzymes, which are coded by gyrA and parC genes, thus any mutation to the genes may affect the drug effectiveness. The objective of the study was to characterize gyrA and parC genes in quinolone-resistant E. coli isolates and correlated the mutations with their phenotypic resistance. Materials and Methods: Thirty-two quinolone-resistant (QR) and six quinolone-sensitive (QS) ESBL-E. coli isolates were identified by antibiotic susceptibility and minimum inhibitory concentration tests. Bioinformatics analysis were conducted to study any mutations occurred in the genes and generate their codon compositions. Results: All the QR ESBL-E. coli isolates were identified as multidrug-resistant bacteria. A single point mutation in the quinolone resistance-determining region (QRDR) of gyrA, at codon 83, caused the substitution amino acid Ser83Leu. It is associated with a high level of resistance to nalidixic acid. However, double mutations Ser83Leu and Asp87Asn in the same region were significantly linked to higher levels of resistance to ciprofloxacin. Cumulative point mutations in gyrA and/or in parC were also correlated significantly (p<0.05) to increased resistance to ciprofloxacin. Conclusion: Together, the findings showed that the mutations in gyrA and parC genes handled the institution of intrinsic quinolone resistance in the ESBL-E. coli isolates. Thus, vigilant monitoring for emergence of new mutation in resistance genes may give an insight into dissemination of QR ESBL-E. coli in a particular region.